2019
DOI: 10.3390/nu11061354
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between School Gardens, Food Literacy and Mental Well-Being in Youth Using Photovoice

Abstract: The goal of the project was to gain an understanding of the relationships between secondary school youth experiences in school gardens and their mental well-being. Over the course of five months, sixteen youths participated in a photovoice research project in which they expressed their personal experiences about food and gardening through photography and writing. The aspects of secondary school youths’ life experiences affected by exposure to school gardens and their impact upon their well-being were identifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
17
0
4
Order By: Relevance
“…Meanwhile, the average instrument used SHOWed documentation and interview techniques. Through photovoice, the average research results obtained were close to the truth of the hypothesis, which was by the purpose of photovoice to improve understanding, and the level of one's critical thinking of images [9,13,42,44,46,47,49].…”
Section: Resultssupporting
confidence: 61%
“…Meanwhile, the average instrument used SHOWed documentation and interview techniques. Through photovoice, the average research results obtained were close to the truth of the hypothesis, which was by the purpose of photovoice to improve understanding, and the level of one's critical thinking of images [9,13,42,44,46,47,49].…”
Section: Resultssupporting
confidence: 61%
“…The current study suggests that the benefits of healthy cooking interventions for youth may extend beyond diet and nutrition. Previous research has similarly demonstrated the mental health benefits of youth gardens (47,48) , with one recent study indicating that youth associate feelings of relaxation with gardening, growing food and cooking (47) . Earlier research has also determined that self-reported cooking ability is positively associated with better family connections, greater mental well-being and lower levels of self-reported depression among adolescents (23) .…”
Section: Discussionmentioning
confidence: 93%
“…School gardens have become a common health promotion strategy to increase FV intake in the U.S. In the past two decades, numerous studies have examined the effects of school gardens on psychosocial variables, FV intake, food literacy, and mental health in children [19][20][21][22][23][24]. Several experimental studies [25,26] have shown that gardening is linked to lower obesity levels in adults, however few studies have reported on the effects of gardening on obesity and related health measures in children [27].…”
Section: Introductionmentioning
confidence: 99%